Comparison of pramipexole and levodopa/benserazide combination therapy versus levodopa/benserazide monotherapy in the treatment of Parkinson’s disease: a systematic review and meta-analysis - Jiang, De-Qi; Zang, Qing-Min; Jiang, Li-Lin; Wang, Yan; Li, Ming-Xing; Qiao, Jing-Yi (Naunyn-Schmiedeberg's archives of pharmacology, 2021)
The purpose of this research was to evaluate the clinical efficacy and safety of pramipexole plus levodopa/benserazide (P+LB) combination therapy in the treatment of Parkinson’s disease (PD) compared to that of LB monotherapy, in order to confer a reference for clinical practice. Randomized controlled trials (RCTs) of P+LB for PD published up to April 2020 were retrieved. Heterogeneity and sensitivity analysis were executed. Twenty-nine RCTs with 3017 participants were included. Clinical efficacy of P+LB combination therapy was significantly better than LB monotherapy (RR 1.27, 95% CI 1.22 to 1.32, P <0.00001). Compared with LB monotherapy, the pooled effects of P+LB combination therapy on UPDRS score were (SMD −1.41, 95% CI −1.71 to −1.11, P <0.00001) for motor UPDRS score, (SMD −1.65, 95% CI −2.25 to −1.04, P <0.00001) for activities of daily living UPDRS score, (SMD −2.20, 95% CI −3.32 to −1.09, P =0.0001) for mental UPDRS score, and (SMD −1.60, 95% CI −2.06 to −1.15, P <0.00001) for complication UPDRS score. The HAMD score showed significant decrease in the P+LB combination therapy compared to LB monotherapy (SMD −1.32, 95% CI −1.80 to −0.84, P <0.00001). In contrast to LB monotherapy, P+LB combination therapy decreased the number of any adverse events obviously in PD patients (RR 0.53, 95% CI 0.45 to 0.63, P <0.00001). In conclusion, P+LB combination therapy is superior to LB monotherapy for improvement of clinical symptoms in PD patients. Moreover, the safety profile of P+LB combination therapy is better than that of LB monotherapy. Further well-designed, multi-center RCTs needed to identify these findings.